(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the author examines the legal framework of public administration in the sphere of land relations is one of the most important institutions of the exercise and protection of land rights of land users and land owners, as the rules of the land law, the content, functions, forms and methods of state regulation of land relations in the context of the priority the rights and freedoms of land owners and land users. Keywords: earth, land and legal relations, law, government, management.